Peran Kompetensi Guru dalam Meningkatkan Motivasi Belajar Akidah Akhlak Peserta Didik pada Lembaga Pendidikan Islam - Saputra, Doni (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study aims to analyze the role of teacher competence in enhancing student learning motivation in the Akidah Akhlak subject for grade X at MAN 2 Kediri. The competencies assessed include pedagogical, professional, social, and personal competence. This research employs a qualitative approach using observation, interviews, and documentation. The findings reveal that teachers with strong competencies can design engaging lessons, create a conducive classroom environment, and apply varied and relevant teaching methods suited to student characteristics. Furthermore, parental support, adequate learning facilities, and ongoing professional training serve as key supporting factors in increasing learning motivation. Overall, the findings confirm that teacher competence plays a crucial role in fostering students’ intrinsic motivation, thereby encouraging active engagement and a deeper understanding of Akidah Akhlak values.